QT/RR Coupling and Gender Differences - Halámek, Josef; Jurák, Pavel; Lipoldová, Jolana; Leinveber, Pavel (Computing in cardiology, 2010)
Data provided by THEW was used to test QT gender differences. Three QT/RR models were used during analysis: a transfer function model (TRF), a model based on exponential weighting of RR intervals (EXP), and an EXP model with additive direct coupling with RR intervals (EXPDC). Data from 81 men and 73 women was analyzed.Women have a significantly higher QTc (p<10(-6)), steeper Gain(L) (QT/RR slope, gain for slow RR variability, p<0.01), faster τ (QT adaptation, p<0.05), higher Gain(F) (gain for fast RR variability, immediate change of QT, p<0.05) and higher QT random variability (p<0.05).The higher prevalence of arrhythmias in women, given by longer QTc, is compensated to some extent by a higher level of Gain(F) and faster τ. The proarrhythmic influence of drugs may originate in a change of Gain(L), Gain(F) or τ without any change in QTc.